Water Quality Profile of Swan River Himachal Pradesh, India using GIS - Sharda, A. K.; Sharma, M. P.; Dumyat, Pankaj (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
To meet the ever increasing demand of drinking water, a number of shallow tube wells are used to draw the water from upper aquifers of Swan river. In most parts of the river catchment, the current ground water extraction is exceeding the recharge rate causing the rapid depletion of shallow ground water, resulting in serious environmental hazards like land subsidence during the dry season flow and very low dilution levels in the surface water. The water becomes polluted due to domestic and industrial waste water discharges. The present paper aims to study a water quality map of Swan River based on the computations of the National Sanitation Foundation Index (NSFWQI) and the Overall Index of Pollution (OIP) using water quality data from July to December 2012. A GIS tool has been used to prepare a water quality map of the study stretch (as a function of distance) along upstream and downstream from the pollution sources. The water quality map can help planners and designers make a quantitative assessment of the problem and better suggest long term measures to improve the health of the river. DOI: http://dx.doi.org/10.3126/hn.v13i0.10045 HYDRO NEPAL Journal of Water, Energy and Environment Issue No. 13, July 2013 Page: 64-69